Identification of the Misconception Levels of Students in Several Public Senior High School in Jember on Straight Motion Material Through Graphical Representation Approach and CRI - Alda Rahma Islamey Felita; I Ketut Mahardika; Singgih Bektiarso (Pascasarjana, Mataram University, 2023)
Misconception is one of the problems faced by many students in learning physics. Misconception is a deviation from the actual concept and can be said to be an understanding of the wrong concept so that it is contrary to the concept set by the experts. Almost all materials in physics learning do misconception, one material that is considered necessary is straight motion. This research aims to identify the level of students' misconception in solving straight motion problems through a graphical representation approach and CRI (Certainty of Response Index). The method used is descriptive qualitative analysis. The research subjects were students of class X IPA in several SHS in Jember. Data collection is done by observation, test, and interviews. The results of data analysis showed that the average percentage of misconceptions of class X students of several SHS in Jember on straight motion materials through a graphical representation approach and CRI was 35.05%. This shows that the level of misconceptions is in the medium category. It is hoped that the teacher can analyze the initial conception to students so that misconceptions can be overcome immediately